Sistem Pendukung Keputusan Pemilihan Sales Provider Terbaik Menggunakan Kombinasi Rank Order Centroid dan TOPSIS - Saputri, Irana; Puspaningrum, Ajeng Savitri (Journal of Information System Research (JOSH), 2024)
Selecting the best salesperson requires a strategic approach that includes an in-depth evaluation of salesperson capabilities and qualifications. The main problem in selecting the best salesperson often lies in the difficulty of finding individuals or teams who have a balance between technical skills, communication skills, and a solid sales track record and the lack of an objective selection model. This study aims to apply effective SPK in selecting the best sales provider by utilizing a combination of centroid and TOPSIS rank order methods to produce objective and accurate recommendations regarding Sales Providers that best suit the company's needs and priorities. This research has important significance in providing a systematic and data-driven approach to selecting the best sales provider, which can improve the efficiency and effectiveness of the decision-making process. The ranking results show that Risman Ardiansyah managed to occupy the first position as the best sales provider with the highest score of 0.94, showing superior performance in all assessment criteria. Al Aziz followed in second place with a score of 0.923, reflecting an almost comparable performance. M Dandi was in third place with a score of 0.8162, followed by Ni Sayu Kade with a score of 0.765 in fourth place. Faizal Azhar occupies the fifth position with a score of 0.6738. These results show that Risman Ardiansyah is the sales provider that best meets expectations based on the criteria used in the evaluation.